God, love, and death of Trunyan Village - Audyandari, Ni Kadek Niyanda (Life and Death: Journal of Eschatology, 2024)
Background: Trunyan Village is a traditional village on the shores of Lake Batur in Bali, Indonesia. The village has unique funeral traditions and religious beliefs. The "Death Penalty Society" is a specialised burial system where bodies are placed on the ground and surrounded by bamboo. The adore and fondness we appear to others can moreover bring meaning and bliss to our lives, indeed as we persevere melancholy and loss. It is critical to keep in mind that seeing God, adoration and passing are intensely impacted by one's culture, religion, traditions and individual views. Method: The method used is qualitative content analysis, interpreted using Goffman's Framing theory. This approach examines how structured narratives in documents and previous research about Trunyan Village influence perceptions of god, love, and death. Findings: In the context of Trunyan Village, the concepts of God, love and death can have unique meanings and are influenced by local traditions and beliefs..God and love from Trunyan village can be seen in their family relationships with the living and the dead, as they still believe in their ancestors..The love and death of the Terunyan people can be seen from their very unique funeral practices, where they say that the corpse or human body that has died will not emit odour and by doing mepasah is the only way for humans to get a good place in the afterlife. Why there is no ngaben tradition in Trunyan, only mapasah and mendem sawa, is because their culture and traditions have been passed down from generation to generation, and their understanding of the funeral process is better than the ngaben tradition. Conclusion: Back to the traditions and culture that influence why Trunyan village prefers to carry out mepasah and mendem sawa funerals. It can be concluded that the funeral tradition of mepasah or mendem sawa carried out in Trunyan village is a tradition carried out from generation to generation from their ancestors, which is a funeral activity that thinks about the concept of humanity where they have an understanding that if the human body has died it will not smell and with the taru menyan tree that grows in the setra or grave that protects the corpse from pungent odours and by covering the corpse with bamboo to protect it from wild animals. Novelty/Originality of this article: Through qualitative content analysis and Goffman's Framing theory, this study explores the meaning of God, love, and death in the context of local traditions. The proposed model includes a digital interactive platform and mobile application to preserve and disseminate knowledge about these cultural practices.